2010
DOI: 10.1111/j.1365-2591.2010.01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three different rotary files to remove gutta‐percha and Resilon from root canals

Abstract: No system removed the root filling materials entirely. Mtwo Retreatment files required less time to remove root filling material than the other instruments. Resilon was removed significantly better from the canal walls than gutta-percha, irrespective of the rotary instruments used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
91
0
12

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 26 publications
7
91
0
12
Order By: Relevance
“…Several techniques have been proposed for removing root filling material, but none have shown the ability to remove gutta-percha and sealer completely from canal walls 8,9,11 . The removal of gutta-percha by using hand instruments is a slow and difficult process, especially when the filling material is well compacted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several techniques have been proposed for removing root filling material, but none have shown the ability to remove gutta-percha and sealer completely from canal walls 8,9,11 . The removal of gutta-percha by using hand instruments is a slow and difficult process, especially when the filling material is well compacted.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of gutta-percha by using hand instruments is a slow and difficult process, especially when the filling material is well compacted. Thus, Ni-Ti rotary instruments are recommended for reducing clinical time and facilitate removal 9,11 . However, in this study, we observed that even after using Ni-Ti rotary instruments specifically developed for retreatment, the filling material was not completely removed from the root canal walls, corroborating the findings of other studies 7,9-11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…112,121 In relation to the instruments used for the removal of filling materials, it has been shown that rotary files with chloroform are more effective than rotary files with heat, 110 K3 than Liberator files, 111 Gates-Glidden than system B 116 and heat than K3. 122 There were no significant differences between Mtwo, Twisted files, Protaper and R-Endo 115 and Hedestrome files in terms of Resilon removal. 118 Resilon has higher solubility than gutta-percha in chloroform and its solubility increases over time.…”
Section: Introductionmentioning
confidence: 91%